PKB, KEGAGALAN PELEMBAGAAN SHARED VALUES DAN DAMPAKNYA - Noor, Firman (Jurnal Penelitian Politik, 2016)
The failure of PKB to institutionalize shared values has provided deep impact of its existence. The presence of vague or indistinct values and party less commitment to establish shared values as working ideology and collective identity are factors behind such a failure. Moreover, the massive role of outsiders in assisting party to create and socialize shared values also becomes the thing that confuses the value infusion process. There are three impacts of the absent of shared values in PKB namely, the establishment of internal factions or grouping based on the spirit of pragmatism, the growth of loyalty dedicated to the figures rather than the party itself which over time overshadows cadres’ loyalty to the party and the appearance of different or gradation in understanding party’s ideology. Those three impacts eventually have become reason behind catastrophic condition that ruins party’s internal solidity.